PENGARUH MOTIVATIONAL BONUSES DAN CORPORATE GOVERNANCE TERHADAP MANAJEMEN LABA - Tasya Renita; Yuliani Almalita (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The objective of this research is to acquire empirical evidence regarding the factors that can affect earnings management in nonfinancial companies listed on Indonesia Stock Exchange. These factors are motivational bonuses, leverage, firm size, size of audit committee, independent commissioner, institutional ownership, managerial ownership, free cash flow, board size, and audit quality. The population used in this research are nonfinancial companies consistently listed on Indonesia Stock Exchange from 2018-2020. This research uses purposive sampling method which the research sample consists of 104 nonfinancial companies listed on the Indonesia Stock Exchange. The results of the data obtained were analyzed using multiple regression method. The results of this research show that motivational bonuses has positive effect on earnings management because the company’s management has opportunistic behaviour to get bonuses with their manipulating company profits. Leverage has negative effect on earnings management because there was surveillance from creditors and investors can minimize earnings management practices, Managerial ownership has positive effect on earnings management because higher managerial ownership can control the company’s management to manipulate financial report, Free cash flow has negative effect on earnings management because the higher of free cash flow indicates the company can manage operational activity well. Audit quality has negative effect on earnings management because public accountant big 4 can detects error from financial statement and reduce earnings management. The other variables have no influence on earnings management.